Beyond the average divorce - Demo, David H.; Fine, Mark A.; Sage eBooks (London : SAGE, 2010)
This work focuses on the fluid nature of divorce and variability to divorce. Rather than a simplistic, static view that emphasizes means and averages in looking at 'typical' family reactions to divorce, the book emphasizes variability, fluidity and change over time in the pre-divorce, divorce, and post-divorce process.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Divorce -- United States; Divorce -- Research -- United States; Electronic books